2017
DOI: 10.3390/polym9120732
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Structural Analysis of Polyaniline and Poly(o-anisidine) Layers Generated in a DC Glow Discharge Plasma by Using an Oblique Angle Electrode Deposition Configuration

Abstract: This work is focused on the structural and morphological investigations of polyaniline and poly(o-anisidine) polymers generated in a direct current glow discharge plasma, in the vapors of the monomers, without a buffer gas, using an oblique angle-positioned substrate configuration. By atomic force microscopy and scanning electron microscopy we identified the formation of worm-like interlinked structures on the surface of the polyaniline layers, the layers being compact in the bulk. The poly(o-anisidine) layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 23 publications
8
71
0
Order By: Relevance
“…Both products exhibited typical FTIR bands of emeraldine form (Table 1) [18,20] even if some differences between the two polymers were found, as already observed by Junker and co-workers [9]. Interestingly, the 1070 cm −1 IR band characteristic of emeraldine salt form of PANI was present in both polymers (protonated NH + ), while only pDANI showed the presence of the 1405 cm −1 band, related to C-N + [40]. Moreover, pDANI displayed bands attributed to para substitutions in benzene ring whilst meta substitutions were present in PANI.…”
Section: Ftirsupporting
confidence: 76%
“…Both products exhibited typical FTIR bands of emeraldine form (Table 1) [18,20] even if some differences between the two polymers were found, as already observed by Junker and co-workers [9]. Interestingly, the 1070 cm −1 IR band characteristic of emeraldine salt form of PANI was present in both polymers (protonated NH + ), while only pDANI showed the presence of the 1405 cm −1 band, related to C-N + [40]. Moreover, pDANI displayed bands attributed to para substitutions in benzene ring whilst meta substitutions were present in PANI.…”
Section: Ftirsupporting
confidence: 76%
“…As shown in Figure 5 (a), the morphology of the nanocomposites consists of 3 particle shapes namely spheres, chunks, and worm-like structures. Sequentially, these shapes describe the Fe3O4 nanoparticles, AC [31,32], and PANI [33]. Qualitatively, it is observed that the sphere of Fe3O4 tends to agglomerate.…”
Section: Resultsmentioning
confidence: 90%
“…Figure presents the FTIR spectra of the copolymer, IWP, and COIW. The FTIR spectrum of the copolymer (Figure A) shows the characteristic bands of the poly(aniline‐ co ‐anisidine) . The N─H and C═N stretching vibrations appeared at 3403 and 1622 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1A) shows the characteristic bands of the poly(aniline-coanisidine). [25][26][27] The N─H and C═N stretching vibrations appeared at 3403 and 1622 cm −1 , respectively. C═C stretching bands for the quinonoid rings observed at 1564 cm −1 and those for benzenoid groups emerged at 1506 and 1457 cm −1 .…”
Section: Electrochemical Measurementmentioning
confidence: 99%